Job characteristics as determinants of job satisfaction and labour mobility - Thomas Cornelißen (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
This paper investigates the effects of detailed job characteristics on job satisfaction, job search and quits using data from the German Socio-Economic Panel (GSOEP) in a fixed effects framework. Using a factor analysis, seventeen job characteristics are reduced to seven factors that describe different aspects of a job, which are qualified as status, physical strain, autonomy, advancement opportunities, social relations at the work place, work time and job security. The effects of these factors on job satisfaction, job search and quits differ. For example, job insecurity reduces job satisfaction, increases the subjective probability of job search but it decreases quits. In circumstances of higher job insecurity it seems to be hard to find a job to quit into. Regressing job satisfaction, job search and quits on the detailed job characteristics shows that, when judging from the number of statistically significant coefficients, the job characteristics explain satisfaction best, while it is harder to explain job search and quits by these characteristics. Job satisfaction, however, is confirmed as a strong predictor of job search and quits after controling for both, individual fixed effects and a set of detailed job characteristics.
Keywords: C23; J62; J28; 330; job satisfaction; job mobility; quits; job search; fixed effects